Historical Overview of Poultry in Japan - Atsushi Tajima (The Journal of Poultry Science, 2023)
To meet the strong quantitative demands for poultry products with high sanitary standards soon after World War II, the Japanese poultry industry experienced a rapid expansion period. However, it should be remembered that the post-war flourishment of the Japanese poultry industry was built on a solid academic and educational platform that took several pre-war decades to construct. In addition, poultry play a special cultural role in Japanese society. In this review, poultry in Japan is illustrated from the following three historical viewpoints: 1) development of the Japanese poultry industry; 2) academic and educational contributions to the poultry industry in Japan; and 3) ritualistic, mythic, and artistic attributes of poultry that are deeply embedded in Japanese society.